Innovative methods of teaching youth polytechnic students in Kenya - Chege, N.W. (My University, 2013)
Interaction with instructors drawn from many TVET institutions in Kenya has revealed that the methods of teaching commonly taught to the instructors during their training, are not effective. Most of those methods are designed for people that have good communication skills among other skills. The purpose of this paper is to evaluate the traditional methods of teaching youth polytechnic students as well as multimedia teaching and to suggest other teaching methods that may be used to effectively impart knowledge and skills to these students. Teaching includes two major components, one of sending and the other, receiving information. Innovative methods are those methods that convey the knowledge and skills intended in a way that makes the sending and receiving of the information effective and efficient. The use of innovative methods in the youth polytechnics has the potential not only to improve education, but also to improve students‟ communication and interaction skills that will eventually eradicate the tribal animosities that has derailed development progress in Kenya and negatively affected human advancement.
Keywords: Innovation; teaching methods; TVET institutions; Kenya